Communicating content: development and evaluation of icons for academic document triage through visualisation and perception. Issue 9 (1st September 2016) - Mavri, Aekaterini; Loizides, Fernando; Zantides, Evripides
ABSTRACT: This work seeks to identify key features and characteristics for the design of icons that can support the tasks of information seekers in academic document triage interfaces. Such icons are meant to act as visual links to the specific elements or sections in an academic document. We suggest that icons in triage interfaces are better able to communicate information, provide feedback and enable faster user interactions than text, particularly in mobile-based interfaces. Through investigation of visualisation and perception processes, we are able to propose five primary icon categories, the two most dominant being iconic and symbolic : iconic representations mostly apply to graphically and spatially distinct document elements (i.e. Title, Abstract, Tables and Figures), externalising the elements' surface propositions. Symbolic representations are largely associated with elements of greater semantic value (Introduction, Conclusion, Full text and Author), drawing upon the elements' deep propositions.